"On shore of Lake" man with logs and pulley system, Hovland (Cook County Historical Society, 8 S Broadway, Grand Marais, MN 55604, www.cookcountyhistory.org)
d2764e0138753e5670563722d7f24860
United States
Minnesota
Cook
Hovland
d2764e0138753e5670563722d7f24860
Keywords: Hovland, MN; Camp S-62; Company 722; CCC; Civilian Conservation Corps; civil service; public service employment; logging; Civilian Conservation Corps (U.S.); Labor